PENGEMBANGAN PROFESIONAL BERKELANJUTAN BAGI GURU PAUD - Muktiono Waspodo (Jurnal Ilmiah Visi, 2012)
In establishing an advanced civilization, early childhood education has a very important contribution. This article discusses how the PAUD teachers should perform their job professional by providing educational services for the early age children properly. As science and technology are developing fast influencing the people’s needs including the early age children, the teacher should keep increasing their knowledge and skills continously. One thing emphasizes in this article that the early age children need fun learning by joyful playing. The teacher’s ability to fulfill this need will enable him/her to stimulate the children’s motoric, emotional, and intellectual development This article emphasizes how the continous professional development performed by the teacher individually or the responsible institution. The article suggests a number of ideas how to plan and implement such a program.